2007
DOI: 10.1074/jbc.m705178200
|View full text |Cite
|
Sign up to set email alerts
|

ATR Pathway Is the Primary Pathway for Activating G2/M Checkpoint Induction After Re-replication

Abstract: DNA replication is tightly controlled to ensure accurate chromosome duplication and segregation in each cell cycle. Inactivation of Geminin, an inhibitor of origin licensing, leads to rereplication in human tumor cells within the same cell cycle and triggers a G 2 /M checkpoint. We find that the primary pathway to signal that re-replication has been detected is the ATR kinase and the Rad9-Rad1-Hus1 (9-1-1) clamp complex together with Rad17-RFC clamp loader. ATM kinase and the Mre11-Rad50-Nbs1 complex do not ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 45 publications
8
56
0
4
Order By: Relevance
“…Instead, our results suggest that abnormal chromatin structure resulting from aberrant DNA replication due to pre-RC deficiency might be a trigger for S phase checkpoint activation. Recently, chromatin alterations have been shown to play an important role for ATR-checkpoint activation, because deregulation of DNA licensing and alteration of chromatin structure indicated by changes of HP1␣ localization, activate S phase checkpoint signaling cascades (Davidson et al, 2006;Lin and Dutta, 2007;Ayoub et al, 2008). Similar chromatin structural alterations also were observed in Orc2 depletion or carcinogen/replication inhibitor studies, where inhibition of new origin firing, replication/chromatin structural alterations, checkpoint activation, and reduced replication rates were reported (Prasanth et al, 2004b;Conti et al, 2007a).…”
Section: Pre-rc Deficiency and Atr-dependent Checkpoint Activationsupporting
confidence: 50%
“…Instead, our results suggest that abnormal chromatin structure resulting from aberrant DNA replication due to pre-RC deficiency might be a trigger for S phase checkpoint activation. Recently, chromatin alterations have been shown to play an important role for ATR-checkpoint activation, because deregulation of DNA licensing and alteration of chromatin structure indicated by changes of HP1␣ localization, activate S phase checkpoint signaling cascades (Davidson et al, 2006;Lin and Dutta, 2007;Ayoub et al, 2008). Similar chromatin structural alterations also were observed in Orc2 depletion or carcinogen/replication inhibitor studies, where inhibition of new origin firing, replication/chromatin structural alterations, checkpoint activation, and reduced replication rates were reported (Prasanth et al, 2004b;Conti et al, 2007a).…”
Section: Pre-rc Deficiency and Atr-dependent Checkpoint Activationsupporting
confidence: 50%
“…It also should be noted that Gem79-130 had little effect on Chk1 phosphorylation induced by GST-Cdt1, suggesting that the checkpoint pathway effectively repressed repetitive origin firing under these conditions. Thus, these observations suggest that there are at least two mechanisms that inhibit the extensive rereplication induced by licensing in S phase, one of which depends on ATR and the Chk1-directed checkpoint machinery Lin and Dutta, 2007;Liu et al, 2007) and the other, which is a Cdt1-induced pathway independent of the checkpoint machinery, as indicated by Davidson et al (2006), which is sensitive to Gem79-130. …”
mentioning
confidence: 99%
“…Recently, it was reported that ATM and Rad3-related (ATR)/Chk1, but not ataxia telangiectasia mutated (ATM)/Chk2, prevents rereplication Lin and Dutta, 2007;Liu et al, 2007), presumably because ATR/Chk1 suppresses the Cdk2 activity required for the initiation of rereplication (Abraham, 2001;Luciani et al, 2004). Checkpoint activation also requires multiple rounds of rereplication, suggesting that activation is induced by the aberrant DNA structures created by multiple replication forks (Davidson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The deletion of the ATR gene causes early embryonic lethality in mice, and the mutation of this gene results in Seckel syndrome, which is characterized by a defective DNA damage response (10)(11)(12). Loss of ATR function also inhibits phosphorylation of downstream effectors such as p53 and Chk1 and leads to apoptosis (6,13). These facts indicate that ATR is essential for cell survival, development, and DNA damage response pathways (10,11).…”
Section: Introductionmentioning
confidence: 94%
“…IR is a well-known inducer of DNA double strand break. Hydroxyurea, a competitive inhibitor of ribonucleotide reductase, blocks DNA replication, resulting in ATR activation (13,32). HCT116-Mock and HCT116-COX-2 cells were exposed to graded doses of IR or hydroxyurea, and then cell viability was monitored by a clonogenic assay.…”
Section: Hct116-cox-2 Cells Containing Elevated Atr Are Resistant To mentioning
confidence: 99%